Molecular genetic risk factors for ischemic stroke in patients with thoracoabdominal malignant tumors - A. A. Korolyova; S. S. Gerasimov; L. N. Lyubchenko (Сибирский онкологический журнал)
Background. Ischemic stroke is one of the most frequent causes of postoperative death in patients with thoracoabdominal malignant tumors. The role of molecular genetic factors of cardiovascular risk in the development of this complication in cancer patients has not yet been studied properly. The identification of genetic determinants of arterial thrombosis will allow predicting an increased risk of ischemic stroke and will create the possibility of pathogenetically justified prevention among carriers of genetic markers of thrombophilia.Aim. To compare the frequency of carriage of procoagulant mutations in the genes of the hemostasis system in cancer patients who have suffered an ischemic stroke and in cancer patients without concomitant cardiovascular diseases.Material and Methods. The non-randomized observational pilot research included 105 patients with thoracoabdominal tumors treated at the Thoracoabdominal Department of N. N. Blokhin National Research Center of Oncology during the period 2018–2019. The study group (n=24) consisted of patients with a history of ischemic stroke or perioperative stroke. The control group (n=81) included patients without concomitant cardiovascular diseases, including a family history. The real time polymerase chain reaction technique was used to determine the gene polymorphisms of blood coagulation.Results. We found a statistically significant difference in the frequency of carriage of the heterozygous variant (GA) mutation of the F2 gene (c2=6,881, p=0,009), homozygous mutation (TT) of the of the ITGA2 gene (c2=15,724, p<0,001), the heterozygous variant (TC) mutation of the ITGB3 gene (c2=3,861, p=0,05) as well as the general frequency of genetic aberrations in these genes between patients with thoracoabdominal malignant tumors, who had ischemic stroke and patients with thoracoabdominal malignant tumors without cardiovascular pathology.Conclusion. Based on the results of the genotyping of factors associated with a high thrombogenic risk, a statistically significant difference in the frequency of occurrence of polymorphisms of hemostasis system genes F2, ITGA2, ITGB3 was revealed between patients with thoracoabdominal malignant tumors, who had ischemic stroke and those without cardiovascular diseases. The role of the genetic factor in the development of ischemic stroke in cancer patients requires further study.